2021
DOI: 10.3390/su132011202
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the Sesame Production Opportunities and Constraints, and Farmer-Preferred Varieties and Traits, in Eastern and Southwestern Ethiopia

Abstract: Sesame (Sesamum indicum L.) is an important oilseed crop with well-developed value chains. It is Ethiopia’s most valuable export commodity after coffee (Coffea arabica L.), contributing to socioeconomic development. The productivity of the crop is low and stagnant in Ethiopia and other major sesame growing regions in sub-Saharan Africa (<0.6 t/ha) due to a multitude of production constraints. The objective of this study was to document sesame production opportunities and constraints, as well as farmer- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The mean grain yield of improved finger millet varieties in Ethiopia is low at 2.7 t/ha [30], compared with 4.74 and 4.79 t/ha reported for Kenya [31] and India [32], respectively. Ethiopia is the primary centre of origin and diversity for finger millet [33]. The finger millet landraces grown by farmers are essential genetic resources that are known to hold useful genetic variation for desirable traits.…”
Section: Introductionmentioning
confidence: 99%
“…The mean grain yield of improved finger millet varieties in Ethiopia is low at 2.7 t/ha [30], compared with 4.74 and 4.79 t/ha reported for Kenya [31] and India [32], respectively. Ethiopia is the primary centre of origin and diversity for finger millet [33]. The finger millet landraces grown by farmers are essential genetic resources that are known to hold useful genetic variation for desirable traits.…”
Section: Introductionmentioning
confidence: 99%
“…Farmers use local sesame cultivars and majority of them do not apply fertilizer (Gedefa, 2010;H. G. Hailu & Mezegebo, 2021;Teklu et al, 2021;Yalew et al, 2020). Research confirmed that the yield of new sesame variety can reach up to 1254 kg (or 1.3 ton)/haunder rainfed conditions (Ahmed, 2008;Habibullah et al, 2021) and 2797.6 kg (or 1.8 ton)/ha under irrigation (Hailu et al, 2018).…”
Section: Evidence That This Is a Problemmentioning
confidence: 95%
“…Sesame production is susceptible to different biotic and abiotic stresses (Pathak et al, 2014). Weather and price fluctuation, and shortage of finance and poor technology adoption have great implications for sesame production and marketing in Ethiopia (Teklu et al, 2021). Studies have reported that sesame growing farmers have been heavily challenged by weather fluctuations due to the global climate change (Taffesse et al, 2012).…”
Section: Key Challenges Affecting the Supply Chainmentioning
confidence: 99%
“…The global sesame production is about 2.211,339 million tons. Sesame production in Ethiopia is about 262,654 tons by 2019 (307 million USD) [4] about 8.96% share in the global sesame market [5]. Sesame productivity in western Tigray is within the range of 2044 kg/ha -400 kg/ha while highly variable with and without the application of insecticides 651 kg/ha, average [5] variability with sesame breed, plantation location, use of fertilizers and agricultural practices with an average yield obtained 400 kg/ha [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sesame production in Ethiopia is about 262,654 tons by 2019 (307 million USD) [4] about 8.96% share in the global sesame market [5]. Sesame productivity in western Tigray is within the range of 2044 kg/ha -400 kg/ha while highly variable with and without the application of insecticides 651 kg/ha, average [5] variability with sesame breed, plantation location, use of fertilizers and agricultural practices with an average yield obtained 400 kg/ha [4]. Sesame productivity yield is as high as 2044 kg/ha [6] and (1161.5 kg/ha -756.5 kg/ha) regardless of the variation of cultivation year, varieties and agro-climatic condition [7].…”
Section: Introductionmentioning
confidence: 99%